Vascular Plants of the Chimbote Wetlands, Peru - Arana, César (2003)
The vascular flora of Chimbote’s wetlands (09°05’51"S; 78°32’52"W) is composed of 18 families and 41 species. Sixty one percent of the species are Magnoliopsida and 39% belong to the Liliopsida. Families with the largest number of species are Poaceae, Cyperaceae and Asteraceae. The dominant growth forms are herbs (85%), followed by shrubs (10%). A comparison with coastal wetlands of Lima, shows that Chimbote has more species that Medio Mundo (16 species) and El Paraíso (25) but less that Los Pantanos de Villa (66). A cluster analysis found greater similitude with Los Pantanos de Villa. In Chimbote's wetland is found four types of plant communities. The greater species diversity is found in the Lacramarca river’s outlet.